2015
DOI: 10.1136/bjophthalmol-2014-306237
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-functional correlation of fundus autofluorescence in Stargardt disease

Abstract: Our data suggest that NIR-FAF patterns correlate with morpho-functional outcomes in eyes affected by Stargardt disease. Longitudinal investigations are warranted to assess more precisely the actual contribution of NIR-FAF in the clinical characterisation of Stargardt disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…A correlation was found between the foveal NIR-AF pattern and vision acuity in Stargardt patients. 31 Cideciyan et al suggested the importance of melanin-dependent NIR-AF to follow the progression of the early-stage of ABCA4associated retinal disease. 32 RPE melanin plays a great role in the pathology and diagnosis of Stargardt disease.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation was found between the foveal NIR-AF pattern and vision acuity in Stargardt patients. 31 Cideciyan et al suggested the importance of melanin-dependent NIR-AF to follow the progression of the early-stage of ABCA4associated retinal disease. 32 RPE melanin plays a great role in the pathology and diagnosis of Stargardt disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are only estimates of the true size of these regions. The use of color fundus photographs, fundus autofluorescence, and OCT is well established in the assessment of the atrophic area; 24 29 however, they are unable to differentiate regions of normal and subnormal function. Similar to retinal imaging, we have demonstrated variability in the assessment of the size of the regions with DS or NS LDC.…”
Section: Discussionmentioning
confidence: 99%
“…This image was used to evaluate the preservation of the ellipsoid zone (EZ) through the fovea [57] and the possible foveal sparing from the disease [38]. A cube of OCT scans was then obtained in high-speed mode with the automated real-time mode activated and set to 10 (creating a mean image of ten repeated identical B-scans to improve signal-to-noise ratio).…”
Section: Methodsmentioning
confidence: 99%